High elevation food preparation: consumer assessment and toolkit development - Engelhardt, Heidi, author; Bunning, Marisa, advisor; Van Buiten, Charlene, committee member; Hyatt, Doreene, committee member (Colorado State University. Libraries, 2021)
At higher elevations, reduced air pressure and dry conditions impact food preparation in a multitude of ways. The boiling point of water decreases, the rate of evaporation is higher, and the functionality of leavening agents can be altered. Cooks, bakers, and food scientists alike face challenges in adjusting processing methods and ingredients to ensure desirable results of recipes at various elevations. Current information on food preparation at high elevations lacks consistency and accessibility and often requires using multiple sources that may not be reliable. This leaves the home cook vulnerable to failed recipes and in some cases, foodborne illness. An assessment of consumer cooking, baking, and food preserving practices was needed to identify and prioritize information that could contribute to successful and safe food preparation at higher elevations. To assess these needs, a survey was developed, conducted, and results were analyzed to guide resource development for a high elevation food preparation toolkit. The purpose of the project was to construct useful materials as part of a set of tools to empower home cooks to apply research-based knowledge in Colorado and other high elevation locations in the United States. Developed resources included eight ingredient information sheets, a troubleshooting guide with suggestions for nine food products or methods. A set of presentation slides and two activities with pre- and post-evaluations to measure behavior change are included for county extension agents to use while engaging with their communities. Expanding awareness related to the impacts that higher elevations have on food preparation connects home cooks with food science as well as food safety. In addition to nutritional needs, food related pastimes often serve a greater purpose providing comfort and a rewarding way to cope with stress, promoting general well-being. Success in a high elevation kitchen would include recipes that do not fail as often, have desired taste and texture, and appropriately address food safety. This toolkit can be utilized in many different ways with the goal of helping consumers become more knowledgeable and successful when safely preparing foods at high elevation. We expect these materials to have national usefulness and aid in the development of skills that can be routinely incorporated in food preparation at higher elevations.
Keywords: food safety; high elevation; toolkit; high altitude; food preparation; survey